Kinetic Cytokine Secretion Profile of LPS-Induced Inflammation in the Human Skin Organ Culture - Raanan Gvirtz; Navit Ogen-Shtern; Guy Cohen (MDPI AG, 2020)
Several in vitro models that mimic different aspects of local skin inflammation exist. The use of ex vivo human skin organ culture (HSOC) has been reported previously. However, comprehensive evaluation of the cytokine secretory capacity of the system and its kinetics has not been performed. Objective: the aim of the current study was to investigate the levels and secretion pattern of key cytokine from human skin tissue upon lipopolysaccharide (LPS) stimulation. HSOC maintained in an air−liquid interface was used. Epidermal and tissue viability was monitored by MTT and Lactate Dehydrogenase (LDH) activity assay, respectively. Cytokine levels were examined by ELISA and multiplex array. HSOCs were treated without or with three different LPS subtypes and the impact on IL-6 and IL-8 secretion was evaluated. The compounds enhanced the secreted levels of both cytokines. However, differences were observed in their efficacy and potency. Next, a kinetic multiplex analysis was performed on LPS-stimulated explants taken from three different donors to evaluate the cytokine secretion pattern during 0-72 h post-induction. The results revealed that the pro-inflammatory cytokines IL-6, IL-8, TNFα and IL-1β were up-regulated by LPS stimuli. IL-10, an anti-inflammatory cytokine, was also induced by LPS, but exhibited a different secretion pattern, peak time and maximal stimulation values. IL-1α and IL-15 showed donor-specific changes. Lastly, dexamethasone attenuated cytokine secretion in five independent repetitions, supporting the ability of the system to be used for drug screening. The collective results demonstrate that several cytokines can be used as valid inflammatory markers, regardless of changes in the secretion levels due to donor’s specific alterations.